PERAN KEPEMIMPINAN TRANSFORMASIONAL MEMODERASI DISIPLIN DAN KOMITMEN TERHADAP KINERJA GURU - Daryani, Daryani (Students Journal of Economic and Management, 2012)
The objectif of this research is for testing and describing the transformasional leader role which moderates inflance of work deskription and organisational commitment to word working of state junior high school teachers arond Sragi District,Pekalongan Regency. This research is done by the census methode and is held toword 108 responden or the state Junior High School teachers arond Sragi District,Pekalongan Regency.The research methode uses proporsional sample.The technique of testing data of this research is validity test,by faktor analysis,reability tes by alpha cronbach,fold regresion analysis,tes-t,normalitas,hetero test,and det ermination test. The result of analysis descrission of this research shouws that work discripline has positif and significant influence toword the teachers performance the organisation commitment has positif and significant toword teachers work,transformasional leader has positif and significant influence and the moderation of transformasional leader on work discription and organisastion comitment run down toword teacher performance of state Junior High School around Sragi district,Pekalongan Regency. Key Words: Work discipline,Organisational comitment,Transformational Leader and Teacher Performance